Implementation of internal audit recommendations in the Local Government Authorities (LGAS): A case of Dar es salaam region - Katuli, Hamadi (Mzumbe University, 2024)
A research report submitted in partial /fulfillment of the requirement for award of Master Degree of Science in Accounting and Finance of Mzumbe University